2009
DOI: 10.1016/j.bpj.2009.02.040
|View full text |Cite
|
Sign up to set email alerts
|

Orientation and Dynamics of Peptides in Membranes Calculated from 2H-NMR Data

Abstract: Solid-state (2)H-NMR is routinely used to determine the alignment of membrane-bound peptides. Here we demonstrate that it can also provide a quantitative measure of the fluctuations around the distinct molecular axes. Using several dynamic models with increasing complexity, we reanalyzed published (2)H-NMR data on two representative alpha-helical peptides: 1), the amphiphilic antimicrobial peptide PGLa, which permeabilizes membranes by going from a monomeric surface-bound to a dimeric tilted state and finally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
219
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(236 citation statements)
references
References 44 publications
17
219
0
Order By: Relevance
“…As a consequence, insertion into unfavorably thin membranes should lead to an adjustment of the tilt of the entire TM part. In accordance with theory and previous observations (24,25,40) PDGFR␤-TM indeed adjusts its tilt according to bilayer thickness from 30°in DMPC, to 20°in POPC, to 10°in DEPC. The latter value matches well with the helix crossing angle of ϳ20°of the PDGFR␤-TM dimer structure determined by liquid-state NMR in DPC micelles (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As a consequence, insertion into unfavorably thin membranes should lead to an adjustment of the tilt of the entire TM part. In accordance with theory and previous observations (24,25,40) PDGFR␤-TM indeed adjusts its tilt according to bilayer thickness from 30°in DMPC, to 20°in POPC, to 10°in DEPC. The latter value matches well with the helix crossing angle of ϳ20°of the PDGFR␤-TM dimer structure determined by liquid-state NMR in DPC micelles (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Solid-state 15 N NMR Analysis in Lipid Bilayers-To determine the alignment of the PDGFR␤-TM helix in a proper lipid environment, one-dimensional solid-state 15 N NMR spectra were acquired in macroscopically oriented membrane samples, as they can reveal the molecular orientation and mobility (24,25). By using lipids with different acyl chain lengths for reconstitution, we studied the influence of the membrane thickness on the helix orientation and on the stability of the peptide in the bilayer.…”
Section: Three-dimensional Structure Characterization By Liquidstate mentioning
confidence: 99%
“…S1 and Table S1), we analyzed the helix tilt for each of the transmembrane peptides (21,23). (Although excessive peptide dynamics does complicate the determination of helix tilt for some peptides (24)(25)(26), the problem is mitigated and the dynamics become tractable when only two aromatic residues are present (3,21) and additionally when a polar residue is present (17,21). We therefore estimated the rather minimal dynamics of the K12 and K14 peptides using a principal order parameter (21).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, the longer transmembrane α-helices of rhodopsin are tilted up to 33° with respect to the normal of the bilayer plane presumably because of the hydrophobic mismatch between their length and the thickness of the bilayer [349]. The orientation of transmembrane α-helical hydrophobic peptides has been shown to depend on hydrophobic mismatch in lipid bilayers [197][198][199][200]. As previously postulated [58] and discussed in section 4.1, the orientation of the RDH11-Nter, LRAT-Cter and R9AP-Cter peptides could result from differences between the thickness of the lipid monolayer and the length of these peptides.…”
Section: Effect Of the Lipid Monolayer On Peptide Structure And Its Rmentioning
confidence: 99%
“…In fact, it has been shown that the orientation of transmembrane α-helical hydrophobic peptides is dependent on the hydrophobic mismatch in lipid bilayers [197][198][199][200]. For example, the tilt of a transmembrane peptide was shown to increase from 27 to 35 and 51° with respect to the normal of bilayers of phospholipids containing, respectively, the following decreasing fatty acyl chain lengths : myristoyl (C14:0), lauroyl (C12:0) and dodecanoyl (C10:0) fatty acyl chains [197].…”
Section: Monolayers As a Model Membrane To Study Hydrophobic Transmemmentioning
confidence: 99%